Resilience and Resistance: Indigenous Agency of Hawai’ian Indigene in Lynn Kalama Nakkim’s Mahele o Maui - Kristiawan Indriyanto (IAIN MADURA, 2022)
In recent years, the emergence of indigenous literature contextualizes the historicity of colonialism and the ensuing resistance. This present study articulates how the Native Hawai’ians articulate their resistance against American domination through the resilience of their cultural heritage and advocates for political changes, as is reflected in Lynn Kalama Nakkim’s Mahele o Maui. The study applied an econarratological perspective which foregrounds the reader's active role in reimagining a different socio-cultural perspective of the natural environment from Mahele’s perspective and engaging with other (non-Western) environmental imagination. The theory of resilience and resistance, as stated by Adamson and Molina, underlines how indigenous Hawai’ian tradition manages to persevere and transform through the Western model of narration, a novel. The study explores how Nakkim’s fiction articulates the indigenous epistemology of Aloha Aina to actively resist American domination with the eventual goal of achieving sovereignty and independence. The finding concludes how Native Hawai’ians’ literature has a similar concern with other indigenous struggles in the world, advocative and politically oriented in outlook, echoing their struggle for the right of self-determination and eventual sovereignty.